EGCG Alleviates Obesity-Induced Myocardial Fibrosis in Rats by Enhancing Expression of SCN5A - Yi, Haoan; Liu, Cong; Shi, Jing; Wang, Shuo; Zhang, Haoxin; He, Yongshu; Tao, Jianping; Li, Shude; Zhang, Renfa (Frontiers in Cardiovascular Medicine, 2022)
Object: Obesity is one of the consequences of a long-term high-fat diet (HFD) and could increase the risk of myocardial fibrosis. (-)-Epigallocatechin-3-gallate (EGCG) is the most abundant in green tea and has been reported to have multiple pharmacological activities. However, there is not enough evidence that EGCG has a therapeutic effect on obesity-induced myocardial fibrosis. Our study investigated whether EGCG is a potential drug for obesity-induced myocardial fibrosis. Methods: Obesity-induced myocardial fibrosis rat model was established by HFD feeding for 36 weeks. EGCG was intragastrically administered at 100 mg/kg/d for the last 4 weeks. We evaluated the pathological changes of myocardial fibrosis by tissue pathological staining and collagen quantification. Furthermore, total RNA was extracted from the heart for RNA-seq to identify the changes in the transcript profile, and the relevant hub genes were verified by quantitative real-time PCR and western blot. Results: EGCG significantly relieved HFD diet-induced obesity and alleviated the pathology of myocardial fibrosis. Biochemical analysis showed that EGCG relieved the burden of lipid metabolism and injury to the myocardium. Transcript profile analysis showed that EGCG alleviated obesity-induced myocardial fibrosis by increasing the level of Scn5a in the heart. Furthermore, quantitative real-time PCR and western blot analysis for Scn5a also confirmed this finding. Conclusion: Taken together, these results suggest that EGCG could protect against obesity-induced myocardial fibrosis. EGCG plays an anti-myocardial fibrosis role by regulating the expression of Scn5a in the heart.